Estimation of the resistance to movement of a wheeled tractor train in field tests - Nikolay Berezhnov (Revista Ingeniería UC, 2022)
The purpose of the studio was to determine the movement resistance of a wheeled tractor train taking into consideration the random nature of changes in external operational factors. The research was based on the example of the unit MTZ-80+2PTS-M in the Mariinsky district of the Kemerovo (Russia) in 2021. The method of control dynamometry was used to determine the probabilistic characteristics of the traction resistance of an agricultural trailer and its dependence on the load-speed mode. The studies were carried out on various backgrounds (unsurfaced road, grain stubble and sowing ﬁeld) with a trailer load from minimum to maximum. Authors have studied the energy assessment of a tractor transport unit in relation to speciﬁc natural-production conditions of its operation. Based on the results authors have revealed the inﬂuence of high-speed and load operating modes of a tractor train and determined the operating weight rational values.